Frequency of oral radiographs requested by dental practitioners in patients under health insurance policy coverage referring to radiology centers in Isfahan in 2010 - Ehsan Hekmatian; Shabnam Seyedizadeh (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: The number of radiographies taken from patients has increased in recent years. On the other hand, the radiographic images prescribed for patients have not been evaluated in the country. The aim of the present study was to determine the type of radiographic images prescribed by general dental practitioners and specialists in patients under health insurance policy coverage, referring to the oral and maxillofacial radiology centers in Isfahan in 2010. Materials and methods: In this descriptive cross-sectional study, 2400 prescribed dental radiographs were randomly selected from the archives of Treatment Services Organization. The data of the prescriptions including the dentists' gender and specialty field, patients' age and gender or radiographic image type were extracted and statistically analyzed by chi-squared and linear regression tests (α = 0.05).Results: Most of the radiographic techniques evaluated had been requested by endodontists (408; 17.0%), oral surgeons (404, 16.8%) and orthodontists (362, 15.1%) while 348 (14.5%) belonged to general practitioiners and the rest had been requested by other specialists. Of all the radiographic techniques requested, 47.5% (1141 cases) were bitewing and periapical, 44.3% (1064 cases) were panoramic views, 7.0% (169 cases) were cephalograms and the rest were other types. A total of 65.4% (1569) of the radiographic images had been prescribed for females and 34.6% (831) for males.Conclusion: Bitewing, periapical and panoramic radiographic techniques had the highest request rates in descending order. Endodontists, oral surgeons and orthodontists had the highest request rates. .Key words: Dental, Radiography, Prescriptions